The Imposition of Financial Consequences Due to Force Majeure in Construction Service Agreements - Zubir, Agusman; Wasitaatmadja, Fokky Fuad; Sadino (Audito Comparative Law Journal (ACLJ), 2024)
Force majeure events are likely in Indonesian construction projects due to the country'ssusceptibility to natural disasters. Contractors are particularly vulnerable to defaults like completion delaysand financial losses due to damage. Legal protection through force majeure clauses is crucial. However,some Project Owners hesitate to define force majeure conditions due to a lack of understanding.Researchers aim to clarify force majeure concepts in agreements and construction contracts to ensure legalcertainty for all parties involved. This study employs a qualitative descriptive approach utilizing libraryresearch methods for data collection. Research findings indicate that construction service contract standardsin Indonesia, including those within the PUPR environment, the FIDIC Contract Form, and other projectcontracts, align with expert formulations and relevant regulations regarding the implementation of the ForceMajeure concept. Typically, the allocation of cost consequences resulting from a Force Majeure eventassigns responsibility to the Project Owner as the Creditor, rather than transferring it to the contractor.However, variations can occur based on the parties' agreement, which, if agreed upon, are legally bindingunder the Pacta Sunt Servanda principle, which facilitates the shifting of Force Majeure liability to thecontractor, prompting the contractor to consider it in their offer.